Improving pathways to interdisciplinary and transdisciplinary research for the Arts, Humanities and Social Sciences: first lessons from the SHAPE-ID project - Policy Brief - Vienni Baptista, Bianca; Lyall, Catherine; Ohlmeyer, Jane; Spaapen, Jack; Wallace, Doireann; Pohl, Christian (My University, 2020)
This policy brief presents key issues and challenges for fostering interdisciplinary and transdisciplinary research in Europe, focusing on the participation of the Arts, Humanities and Social Sciences in such research. It provides concrete guidance to policy makers and funding organisations on how to tackle those issues and maximise the participation of the Arts, Humanities and Social Sciences.
Acknowledgments: We are indebted to Joël Graf (National Contact Point, Euresearch, Switzerland) for comments and advice on an early version.
Keywords: Interdisciplinarity; transdisciplinarity; interdisciplinary research; transdisciplinary research; arts; humanities; social sciences; integration; research policy; research funding; science policy; International Integration; Interdisciplinary research; RESEARCH POLICY IMPLICATIONS; interdisciplinary collaboration; transdisciplinary collaboration